The Productivity and Carbon Exchange of an Intensively Managed Pasture in Central Kentucky - Ife Familusi; Maheteme Gebremedhin; Ian Ries; Jacob Brown; Buddhi Gyawali (Atmosphere, 2024)
Intensive pasture management that aims at providing season-long forage while minimizing soil degradation is increasingly becoming an important grazing strategy in Kentucky. Typically, it involves the use of high-yielding warm and cool season forage species that are well suited to local soil and climate conditions, meeting the dual-purpose provision of high nutritional value while remaining resilient to grazing pressure and changing climate. Monitoring carbon exchange is a crucial component for effective pasture management to promote sustainable pastureland management practices. We hypothesized that pasturelands, when intensively managed, would exhibit a small but important CO2 cumulative uptake year-round. We used the Eddy covariance method to measure the net ecosystem exchange of CO2 (NEE) and productivity of an intensively managed pastureland at Kentucky State University Research and Demonstration station from 2015 to 2020. The study has two objectives: to quantify interannual variability in net ecosystem exchange, and examine the controlling environmental factors, in particular temperature, sunlight, and precipitation of NEE. Diurnal and seasonal fluctuations followed typical patterns of carbon uptake and release. Overall, the pasture site consistently was carbon sink except for 2016, in part due to a warmer winter season than usual, sequestering 1394 gCm−2 over the study period. Precipitation and temperature were critical environmental factors underpinning seasonal CO2 uptake and release. Of critical importance was the net carbon uptake during the non-growing season.